Balancing Environmental Protection and Production of Marine Renewable Energy through Maritime Spatial Planning - Soininen, Elina (My University, 2022)
This thesis systemises the legal framework of maritime spatial planning and the implementation of ecosystem-based approach in the European Union. The aim is to assess whether the EU’s Maritime Spatial Planning Directive can work as an instrument to safeguard environmentally safe production of renewable energy at sea. It is discussed whether the MSPD can help resolve the conflicting interests of marine protection and climate change mitigation by producing marine renewable energy. In this thesis it is argued that the Directive is vague in its obligations and leaves too much discretion to the Member States. To answer this question, this thesis also examines the framework of the ecosystem-based approach, which is required by the Maritime Spatial Planning Directive to be applied in the national planning of the Member States. Finally, this thesis seeks to assess how the objectives of marine protection and the promotion of renewable energy can be reconciled in the future. The analysis is built on legal dogmatics in the systematisation of EU legislation. As this thesis ultimately looks to the future and makes recommendations, regulatory theory is also used as a method to develop a framework in which the desired objectives can co-exist. In addition, the ecosystem-based approach is used, as this thesis analyses EU legislation from the ecosystem perspective. The primary object of analysis is the Maritime Spatial Planning Directive and main research material consists of legal literature and official communications by the European Commission. While the promotion of renewable energy often refers to the need to ensure environmental protection, and while the Maritime Spatial Planning Directive requires the application of the ecosystem-based approach, this paper argues that these instruments do not provide adequate protection for the marine environment and thus does not resolve the conflict between the objectives. The obligations are vague, and it is uncertain what the Member States should assess in individual projects and individual areas. Furthermore, it is concluded, that the vague application of the ecosystem-based approach globally does not support the assessment of environmental factors. For maritime spatial planning to successfully work as a means to resolve these conflicts, it should recognise environmental requirements. This thesis argues that the co-existence of these two objectives requires better guidelines on what is expected of the Member States and how these objectives should be weighed in balancing the interests.

Tässä tutkielmassa tarkastellaan Euroopan unionin merialuesuunnittelun oikeudellista kehystä ja ekosysteemiin perustuvan lähestymistavan soveltamista Euroopan unionissa. Tavoitteena on arvioida, voiko EU:n merialuesuunnitteludirektiivi toimia välineenä, jolla turvataan ympäristöturvallinen uusiutuvan energian tuotanto merellä. Keskeistä on tutkia, auttaako direktiivi ratkaisemaan ristiriitaiset intressit, jotka liittyvät meriensuojeluun ja uusiutuvan energian tuottamiseen merellä ilmastonmuutoksen hillitsemiseksi. Tutkielmassa argumentoidaan, että direktiivi on velvoitteiltaan epäselvä ja jättää liikaa harkinnanvaraa jäsenvaltioille. Lisäksi tutkielmassa tarkastellaan myös ekosysteemiin perustuvan lähestymistavan puitteita, sillä merialuesuunnitteludirektiivissä edellytetään, että lähestymistapaa sovelletaan kansallisten suunnitelmien laadinnassa. Lopuksi arvioidaan, miten meriensuojelun ja uusiutuvien energialähteiden käytön edistämisen tavoitteet voidaan sovittaa yhteen tulevaisuudessa. Tutkielman analyysi rakentuu lainopin varaan EU:n lainsäädäntöä tulkiten ja systematisoiden. Koska tutkielmassa suunnataan katse tulevaisuuteen ja annetaan suosituksia, menetelmänä käytetään myös sääntelyteoriaa kehitettäessä puitteita, joissa näitä kahta tavoitetta voidaan edistää rinnakkain. Lisäksi menetelmänä hyödynnetään ekosysteemiin perustuvaa lähestymistapaa, koska tutkielmassa analysoidaan EU:n lainsäädäntöä ekosysteemin näkökulmasta. Analyysin ensisijainen kohde on merialuesuunnitteludirektiivi, ja pääasiallinen tutkimusaineisto koostuu oikeuskirjallisuudesta ja Euroopan komission virallisista tiedonannoista. Vaikka uusiutuvan energian edistämisessä viitataan usein tarpeeseen varmistaa ympäristönsuojelu, ja vaikka merialuesuunnitteludirektiivissä edellytetään ekosysteemiin perustuvan lähestymistavan soveltamista, tutkielmassa väitetään, että nämä instrumentit eivät tarjoa asianmukaista meriensuojelua ja siten eivät voi selventää näiden tavoitteiden välistä konfliktia. Velvoitteet ovat epäselviä ja on epävarmaa, mitä elementtejä jäsenvaltioiden pitäisi arvioida yksittäisissä hankkeissa ja yksittäisillä alueilla. Lisäksi tutkielmassa todetaan, että ekosysteemiin perustuvan lähestymistavan epäjohdonmukainen soveltaminen globaalisti ei sinänsä tue ympäristötekijöiden arviointia. Jotta merialuesuunnittelu toimisi asianmukaisena keinona ratkaista nämä ristiriidat, sen olisi tunnustettava ympäristövaatimukset asianmukaisesti. Jotta nämä molemmat tavoitteet voidaan toteuttaa rinnakkain aiheuttamatta haittaa toiselle, tässä tutkielmassa esitetään, että olisi laadittava paremmat EU-tason suuntaviivat siitä, mitä jäsenvaltioilta tarkalleen odotetaan ja kuinka tavoitteita tulisi painottaa.
Keywords: renewable energy sources, protection of the seas, maritime spatial planning, ecosystem-based approach, sustainable development, biodiversity, EU law uusiutuvat energialähteet, meriensuojelu, merialuesuunnittelu, ekosysteemiin perustuva lähestymistapa, kestävä kehitys, biodiversiteetti, EU-oikeus